Muslim minorities and bank loans between interest and necessity - Shehata, Asmaa Fathy Abdel Azeez (Journal of Islamic Sciences, 2022)
The research aimed at clarify the ruling on Muslim minorities dealing with banks through loans, and to determine the nature of the interest that accrues to them, and the extent to which necessity is considered or not in this issue. The research method is represented in the deductive approach, by comparing the approved schools of jurisprudence, discussing the difference between them, and clarifying the most correct ones. The research concludes with several results, the most important of which are: that Muslim minorities represent a group of people who share the religiosity of Islam, and live in a society in which non-Islamic laws are applied and are less in number than the majority in that society that does not owe this religion, and that lending and bank borrowing with interest are prohibited by Sharia; because they involve usury, and that dealing with Muslim minorities with bank loans is not permissible if they are in a state of capacity and choice, while it is permissible for them temporarily in the case of necessity only if the halal doors are closed in their faces, and with specific restrictions. The expected interest from dealing in usury with regard to those with high incomes among the Muslim minorities is considered an illusory interest, and it is in the right of those in need among them if other permissible ways to achieve it are found, and that the considered necessity is the real necessity that is in the basic matters of life, and it is a permission for Muslim minorities in individual cases only, and does not include matters that are in excess of what life does.